2018
DOI: 10.1002/cncr.31230
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors and survival after breast cancer in the Women's Health Initiative

Abstract: Among women with early stage breast cancer, cardiometabolic risk factors are significantly associated with cardiovascular and other-cause mortality, but not breast cancer mortality. Cancer 2018;124:1798-807. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 57 publications
(143 reference statements)
3
44
1
Order By: Relevance
“…A recent systematic review examined the risk of CVD mortality after breast cancer, and concluded that approximately 2% to 10% of women with breast cancer die of CVD, and that CVD mortality is elevated among women with breast cancer compared with women without a breast cancer history . Similar to women in the general population, traditional risk factors for CVD, such as hypertension and excess adiposity, have been associated with CVD incidence and mortality among survivors of breast cancer . However, to our knowledge, whether breast cancer and its treatment exacerbate these risk factors, contributing to greater increases in CVD risk over time compared with among women without breast cancer, has not been well established to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review examined the risk of CVD mortality after breast cancer, and concluded that approximately 2% to 10% of women with breast cancer die of CVD, and that CVD mortality is elevated among women with breast cancer compared with women without a breast cancer history . Similar to women in the general population, traditional risk factors for CVD, such as hypertension and excess adiposity, have been associated with CVD incidence and mortality among survivors of breast cancer . However, to our knowledge, whether breast cancer and its treatment exacerbate these risk factors, contributing to greater increases in CVD risk over time compared with among women without breast cancer, has not been well established to date.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also have identified endocrine therapy as a predictor of weight gain in survivors of breast cancer, whereas others have not noted this association . Although to the best of our knowledge the consequences of weight gain on CVD among women with breast cancer remain unclear, and could depend on the timing of weight gain relative to the diagnosis of breast cancer, excess adiposity measured at a single time point has been positively associated with CVD incidence and mortality after breast cancer . Thus weight, BMI, and other adiposity measures remain important outcomes to monitor in women with a breast cancer history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular risk factors can be enhanced during cancer treatment and lead to an increased risk of coronary artery disease (CAD) in survivors (Chang, Moudgil, Scarabelli, Okwuosa, & Yeh, 2017a;Chang, Okwuosa, Scarabelli, Moudgil & Yeh, 2017b;Darby et al, 2013;Greenlee et al, 2017;Hague et al, 2014;Marmagkiolis et al, 2016;Weaver, Jessup, & Mayer, 2013). Increased CVD morbidity and mortality may be attributed to preexisting CVD in newly diagnosed cancer patients, cardiotoxicity resulting in decreased ventricular function, and treatment effects that result in increased CVRFs such as dyslipidemia, hypertension, central adiposity, and metabolic syndrome (Azard & Denmark-Wahnefried, 2014;Cespedes Feliciano et al, 2016;Coviello, Knobf, & Laclergue, 2013;Gristina et al, 2015;Simon et al, 2018). Genetic factors that produce variable susceptibility to both cancer treatment and toxicity may also be at play (Buzdar, Marcus, Blumenschein, & Smith, 1985;Patel, 2016;Smit, Noordam, le Cessie, Trompet, & Jukema, 2017).…”
Section: Cardiovascular and Cancer Riskmentioning
confidence: 99%
“…The consequence of a growing population of cancer survivors is that most will end up dying of some cause other than their cancer. Numerous studies of cancer survivors indicate that cardiovascular disease is the most common cause of mortality for patients with the 2 most common cancers diagnosed in the United States, breast cancer and prostate cancer . Studies have also shown that in comparison with individuals without cancer, breast and prostate cancer survivors actually have a greater risk of developing and dying of cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%